Transcriptomic and Drug Discovery Analyses Reveal Natural Compounds Targeting the KDM4 Subfamily as Promising Adjuvant Treatments in Cancer - del Moral-Morales, Aylin; Salgado-Albarrán, Marisol; Ortiz-Gutiérrez, Elizabeth; Pérez-Hernández, Gerardo; Soto-Reyes, Ernesto (Frontiers in Genetics, 2022)
KDM4 proteins are a subfamily of histone demethylases that target histone H3 lysines 9 and 36 trimethylation. These histone marks are associated with transcriptional repression and elongation respectively. Their deregulation in cancer may lead to chromatin structure alteration and transcriptional defects that could promote malignancy. KDM4 proteins are promising drug targets in cancer therapy; however, only a few drugs have been described as inhibitors of these enzymes. Notably, natural compounds are a major source of biologically active substances and many are known to target epigenetic processes such as DNA methylation and histone deacetylation, making them a rich source for the discovery of new histone demethylase inhibitors. Here, using transcriptomic analyses we determined that the KDM4 family is deregulated and associated with a poor prognosis in multiple neoplastic tissues. Also, by molecular docking and molecular dynamics approaches, we screened the COCONUT database to search for inhibitors of natural compounds origin compared to FDA-approved drugs and DrugBank databases. Notably, we found that molecules from natural products presented the best scores in the FRED docking analysis. Molecules with sugars, aromatic rings, and the presence of OH or O- groups favor the interaction with the active site of KDM4 subfamily proteins. Finally, we integrated a protein-protein interaction network to correlate data from transcriptomic analysis and drug discovery screenings to propose FDA-approved drugs that could be used as multitarget therapies or in combination with the potential natural inhibitors of KDM4 enzymes. This study presents an integrative view from a transcriptomic and protein structure perspective, highlighting the relevance of the KDM4 family in cancer and thus proposing a series of natural compounds that could be used as novel treatments for this disease.